Whole genomes reveal multiple candidate genes and pathways involved in the immune response of dolphins to a highly infectious virus. Issue 23 (22nd March 2021) - Batley, Kimberley C.; Sandoval‐Castillo, Jonathan; Kemper, Catherine M.; Zanardo, Nikki; Tomo, Ikuko; Beheregaray, Luciano B.; Möller, Luciana M.
Abstract: Wildlife species are challenged by various infectious diseases that act as important demographic drivers of populations and have become a great conservation concern particularly under growing environmental changes. The new era of whole genome sequencing provides new opportunities and avenues to explore the role of genetic variants in the plasticity of immune responses, particularly in non‐model systems. Cetacean morbillivirus (CeMV) has emerged as a major viral threat to cetacean populations worldwide, contributing to the death of thousands of individuals of multiple dolphin and whale species. To understand the genomic basis of immune responses to CeMV, we generated and analysed whole genomes of 53 Indo‐Pacific bottlenose dolphins ( Tursiops aduncus ) exposed to Australia's largest known CeMV‐related mortality event that killed at least 50 dolphins from three different species. The genomic data set consisted of 10, 168, 981 SNPs anchored onto 23 chromosome‐length scaffolds and 77 short scaffolds. Whole genome analysis indicated that levels of inbreeding in the dolphin population did not influence the outcome of an individual. Allele frequency estimates between survivors and nonsurvivors of the outbreak revealed 15, 769 candidate SNPs, of which 689 were annotated to 295 protein coding genes. These included 50 genes with functions related to innate and adaptive immune responses, and cytokine signalling pathways and genes thought to be involved in immune responses to other morbilliviruses. Our study characterised genomic regions and pathways that may contribute to CeMV immune responses in dolphins. This represents a stride towards clarifying the complex interactions of the cetacean immune system and emphasises the value of whole genome data sets in understanding genetic elements that are essential for species conservation, including disease susceptibility and adaptation.